ANALISIS HASIL PENDAPATAN DAN STRATEGI PEMASARAN INDUSTRI KAPUR (STUDI KASUS PADA KELOMPOK INDUSTRI BATU KAPUR PELITA JAYA DESA MOKONG KECAMATAN MOYO HULU) - Vorismayani, Muhammad Ardiansyah; Fahlia (Jurnal Nusa Manajemen, 2024)
The aim of this research is to analyze income of the lime industry business by formulating appropriate marketing strategies based on SWOT analysis and determining strategies that should be prioritized based on QSPM analysis. The data analysis method used is analyzing production quantities, production costs, receipts, income. Formulate marketing strategies using analytical tools, namely the SWOT matrix and QSPM matrix. The result of this research is an income of IDR57,955,168 per month. The results of the SWOT analysis show that the appropriate strategy to implement is an aggressive strategy with an opportunity score of 2.31 and a strength score of 2.51. Based on the QSPM analysis, the strategy ofdeveloping different types of lime variants is an alternative priority with a total attractiveness value of 6.10 and maintaining product quality and service to consumers with a total attractiveness value of 6.02.